Pure single‐port retzius‐sparing robot‐assisted radical prostatectomy with the da Vinci SP: Initial experience and technique description - Periklis Koukourikis; Ali Abdullah Alqahtani; Woong Kyu Han; Koon Ho Rha (BJUI Compass, 2022)
Abstract Objective To assess the feasibility and safety of pure single‐port (SP) retzius‐sparing robot‐assisted radical prostatectomy (RARP) using the da Vinci SP and describe the technique. Materials and Methods From August 2020 to November 2020, data of 10 consecutive patients with localized prostate cancer, who underwent SP retzius‐sparing RARP, were prospectively collected. Patients demographics, intraoperative variables, postoperative complications, early oncological, and functional outcomes were assessed. Results The patients were aged 46–73 years with a body mass index between 20.3 and 27.4 kg/m2. Prostate volumes ranged from 15 to 47.2 ml, with a median (interquartile range, IQR) PSA level of 7.4 (6.2–9.1) ng/ml. All surgeries were successfully completed without conversion. The median (IQR) operative and console time were 106 (101–109) min and 65 (63–68) min, respectively. The median (IQR) blood loss was 125 (50–150) ml, and one Clavien–Dindo grade I complication occurred. At 3 months, nine patients had undetectable PSA levels and all patients were continent. Conclusions Pure SP retzius‐sparing RARP could be safely performed using the da Vinci SP system, with acceptable surgical times and minimal complications. Future research will evaluate the advantages of this technique over the standard multiport robotic surgery.